The impact of remanufacturing: a partnership between brands and consumers - Barbanti, Juliana de Campos Maia (2024)
This study aims to deepen the understanding of how consumers and brands can cooperate to reach more sustainable levels of consumption in the circular economy. Sustainability and circular economy are topics that have gained relevance throughout the past years as unbounded consumption and inadequate disposal of used products rampantly increase, progressively reducing the availability of raw materials and natural resources and, consequently, expanding the hazardous impact of climate change and trash production. To add up to this equation, recent inflation, and economic uncertainty force consumers to become more aware and conscious of their habits and choices when spending. Therefore, to answer this challenging landscape, a few incumbent brands are timidly piloting different disposal strategies for which they need the cooperation and partnership from consumers to be successful. Thus, this is a case study, through which Ambev’s strategy in Brazil will be investigated both through data obtained from interviews with the company’s managers, and researched data accessed through public company reports and media vehicles to provide an in-depth comprehension of the phenomena and its impact in a real case scenario. It is expected that the understanding developed by the end of this study will generate guidelines through which brands will be able to design effective and valuable interactions with their consumers in the endeavor of partnering towards more sustainable levels of production and consumption.